Questioning the Effectiveness of Indonesia’s Local Government Accountability System - Rahmatunnisa, Mudiyati (Research and Development Agency Ministry of Home Affairs, 2018)
This paper discusses current Indonesia’s local government accountability system which has undergone fundamental change since the reform era. Through a number of regulations, local governments now have to submit reports which include LPPD, LKPj, ILPPD, and LKPD. In line with what have been constructed by many experts, from normative perspective, those reports have the potential to facilitate a sound local government financial management and in turn, make them more accountable. Has current Indonesia’s local government accountability system been effectively implemented? Have these accountability mechanisms delivered their potential benefits as promised and constructed by many experts? In order to critically answer the questions, this study employs qualitative method with theory-driven approach. The data is mainly obtained through conducting meta-analysis through critically reviewing relevant sources or documents. Analysis goes from data reduction, to data organization and to interpretation. Research findings show that Indonesia’s existing local government accountability system has not been effectively implemented and brought all the potential benefits as calculated in both theoretical realm of accountability as well as constructed Indonesian government regulations. The findings of the study are particularly valuable in terms of filling the void on the analysis and information of current practice of local government accountability system in Indonesia’s reform era which have been marred by a number of problems, irregular and incomplete reporting, the absence of enforceability, limited capacity of local governments to produce appropriate reports, corruptive behavior of the auditors, and limited public participation.